Critical Reviews: Biotechnology and Sustainable Industrialisation for National Development - C. C. Ezemba; O. J. Osuala; V. N. Anakwenze (Archives of Current Research International, 2021)
This study aims to educate people about biotechnology and its role in the socio-economic advancement and development of a nation so that they can make informed choices. There is a growing appreciation that nationally, regionally and globally the management and utilisation of natural resources need to be improved and that the amounts of waste and pollution generated by human activity need to be reduced on a large scale. Economic growth provides jobs and income, goods and services and opportunities to improve the standard of living for an increasing world population. It is evident from various reports that, over the years, the requirement of biomass for food, fodder and fuel has been responsible for different types of environmental problems like deforestation, eutrophication, contaminated agricultural fields, etc. The eco-efficiency of industrial bio-products and bioprocesses can provide a basis for moving a broad range of industries toward more sustainable production. However, these applications are occurring as a “thousand points of light”, that is, without a guiding principle or a strategic orientation. It is concluded that biotechnology occupy a very strategic position in the socio-economic advancement and development of the nation in particular and the world at large. Investments therefore should be made on more sustainable and renewable raw materials – a bio-based economy rather than the conventional or the traditional methods so as to provide a cleaner and healthier environment.